The Influence of Liquid Compost of Brown Algae (Sargassum polycystum) Enriched by N, P, K Fertilizer to Chemical Properties of Ultisol Soil and Shallot Production (Allium ascolonicum). - jupita rahmadani; alida alida; razali razali (Universitas Sumatera Utara, 2019)
The aim of this research was to know the influence of brown algae (Sargassum polycystum) enriched by N, P, K fertilizer to the chemical properties of ultisol soil and Alium cepa L. production. This research was conducted in June-October 2017 using non factorial randomized design with 7 treatments and 4 replications ie P0 (Control), P1 (liquid compost (3x aplications) without enriched), P2 (liquid compost (3x aplications + 2 g urea + 5 g SP36 + 0.5 g KCl), P3 (liquid compost (3x aplications + 1 g urea + 2.5 g SP36 + 0.25 g KCl), P4 (liquid compost ( 6x aplications + 2 g urea + 5 g SP36 + 0.5 g KCl), P6 (liquid compost (6x aplications + 1 g urea + 2.5 g SP36 + 0.25 g KCl) The parameters observed were soil pH, N-total, P-available, K-dd, C-organic, dry weight of shoot, and dry weight of bulb.The results showed that brown algae (Sargassum polycystum) enriched by N, P, K fertilizer can increasing the pH of soil, P-available, K-dd, C-organic, dry weight of bulb and dry weight of shoot. The best dose was P2 (liquid compost (3x aplications + 2 g urea + 5 g SP36 + 0.5 g of KCl) to P-available, dry weight of shoot and dry weight of tuber.